EFEKTIVITAS MODUL PEMBELAJARAN BIOLOGI BERORIENTASI INTEGRATED SCIENTIFIC PROCESS UNTUK MENINGKATKAN VOCATIONAL SKILLS SISWA SMA - Wicaksana, Ervan Johan; Maridi, Maridi; Sutarno, Sutarno (Jurnal Pendidikan Biologi, 2017)
The purpose of this research is to know the improvement of vocational skills of Senior High School students after the application of biology learning module oriented Integrated Scientific Process. This study includes experimental research. Data collection in this research using test technique. The sample consisted of one high school class of 60 students divided into 30 control classes and 30 experimental classes. Data analysis using independent sample t test. The result of the research shows that learning module of waste management approach oriented to Integrated Scientific Process has proven effective to be applied in science learning which is proven from t test result t that is t count> t table (6,929> 2,002) and p <0,05 (0,00 <0, 05).